Effective School Literacy Culture and Learning Outcomes: The Multifaceted Leadership Role of the Principal - Kierstead, Matthew; Georgiou, George; Poth, Cheryl; Mack, Emily (Alberta Journal of Educational Research, 2023)
The purpose of this study was to explore the multifaceted leadership role an effective principal assumed in the deployment of evidence-based literacy practices in her school. We conducted a mixed methods case study integrating the lived experiences of 11 school staff (principal, learning support teacher, and classroom teachers) with the reading scores of 122 Grade 1 to 3 students in Alberta (Canada). A merged mixed analysis strategy revealed four interdependent influences pointing to key contributions of the principal in igniting awareness, developing expertise, creating momentum, and leveraging data in relation to literacy school practices. Our findings shed light on the complexity inherent in the roles of principals and their interactions with others in developing evidence-based literacy school cultures that improve students’ performance. Keywords: leadership, mixed methods, principal, reading. L'objectif de cette étude était d'explorer le rôle de leadeurship à multiples facettes qu'une directrice d'école efficace a assumé dans le déploiement de pratiques de littératie fondées sur des données probantes dans son école. Nous avons mené une étude de cas à méthodes mixtes intégrant les expériences vécues de 11 membres du personnel de l'école (directrice, enseignant de soutien à l'apprentissage et enseignants) et les résultats en lecture de 122 élèves de la première à la troisième année de l'Alberta (Canada). Une stratégie d'analyse mixte fusionnée a révélé quatre influences interdépendantes soulignant les contributions clés de la directrice d'école à la sensibilisation, au développement de l'expertise, à la création d'une dynamique et à l'exploitation des données en relation avec les pratiques scolaires en matière d'alphabétisation. Nos résultats mettent en lumière la complexité inhérente aux rôles des directions d'école et à leurs interactions avec d'autres personnes dans le développement de cultures scolaires fondées sur des données probantes qui améliorent le rendement des élèves. Mots clés : leadeurship, méthodes mixtes, direction d'école, lecture.